Acid fast bacilli detected in the oral swab sample of a pulmonary tuberculosis patient - Reiska Kumala Bakti; Ni Made Mertaniasih; Diah Savitri Ernawati; Bagus Soebadi; Priyo Hadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Tuberculosis (TB) is an infectious disease that persists as a health problem worldwide. Mycobacterium tuberculosis, as an etiological agent, is transmitted from infected to uninfected individuals via airborne droplet nuclei. Oral health care workers or dental practitioners may be at high risk of TB infection because of their close proximity to infected individuals during treatment procedures. Simple and rapid screening of mycobacterium tuberculosis in the oral cavity is necessary in order to prevent transmission of infection. Purpose: To investigate the presence of acid-fast bacilli in the buccal mucosa of pulmonary TB patients. Methods: Nineteen pulmonary TB patients of both sexes, ranging in age from 19 to 74 years old participated in this study. The diagnosis of tuberculosis was performed by clinical symptom assessment and supporting examination, including acid-fast bacilli on sputum examination. Two buccal mucosa swabs taken from pulmonary TB patients were collected for acid fast bacilli direct smear by Ziehl Neelsen staining. Results: With regard to mycobacterium tuberculosis, acid-fast bacilli presented in 10.5% of the oral buccal mucosa swabs of subjects, whereas in the sputum specimens, bacilli were found in 52.6% of subjects. Conclusion: Acid-fast bacilli can be found in the buccal epithelial mucosa of pulmonary tuberculosis patients, although its presence was very limited.